Pertumbuhan dan Produksi Tanaman Kacang Tanah (Arachis hypogaea L.) dengan Pemberian Pupuk Kascing dan Pupuk Hayati Petrobiofertil - Putri Dian Annisa; Dermawan Hutagaol; Ahmad Sofian (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
Peanuts (Arachis hypogaea L.) are the second most important legume crop in Indonesia after soybeans. Providing Vermicompost and Petrobiofertil Biological Fertilizer can increase plant growth and production and can also improve the chemical and biological properties of the soil. This research aims to determine the response to the application of vermicompost fertilizer and petrobiofertile biological fertilizer and their interaction on the growth and production of peanuts (Arachis hypogaea L.). The research was carried out on the land of Karang Rejo Pasar I Village/Subdistrict, Stabat District, Langkat Regency, North Sumatra Province with an altitude of ± 25 meters above sea level. This research was conducted from April to July 2023. This research used a Factorial Randomized Block Design with 2 factors studied and 3 replications where the first factor was Vermicompost (K) with 3 levels, namely: K0 (Control), K1 (2 Kg/ plot), K2 (4 Kg/plot) and the second factor is Petrobiofertil Biological Fertilizer (H) which consists of 4 levels, namely: H0 (Control), H1 (12 g/plot), H2 (24 g/plot), H3 ( 36 g/plot). The parameters observed were plant height (cm), pod weight per plot (g), pod weight per sample plant (g), weight of 100 dry seeds per plot (g). The results of the research showed that the application of vermicompost fertilizer had a very significant effect on the observed parameters such as plant height, pod weight per plot, pod weight per sample plant. The application of Petrobiofertil Biological Fertilizer had a very significant effect on all observed parameters such as plant height, pod weight per plot, pod weight per sample plant, weight of 100 dry seeds per plot. Meanwhile, the interaction of Vermicompost and Petrobiofertil Biological Fertilizer only had a significant effect on the parameters of plant height and pod weight per plot